Transcriptional Analysis of the Effects of Gambogic Acid and Neogambogic Acid on Methicillin-Resistant Staphylococcus aureus - Hua, Xin; Jia, Yue; Yang, Qin; Zhang, Wanjiang; Dong, Zhimin; Liu, Siguo (Frontiers in Pharmacology, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) infection is a major threat to human health, as this bacterium has developed resistance to a variety of conventional antibiotics. This is especially true of MRSA biofilms, which not only exhibit enhanced pathogenicity and but also are resistant to most antibiotics. In this work, we demonstrated that two natural products with antitumor activity, namely, gambogic acid (GA) and neogambogic acid (NGA), have significant inhibitory activity toward MRSA. GA and NGA can not only effectively inhibit planktonic MRSA strains in vivo and in vitro but also have strong inhibitory effects on MRSA biofilms formation. By transcriptome sequencing, Q-RT-PCR and PRM, we found that GA and NGA could reduce the expression of S. aureus virulence factors by inhibiting the saeRS two-component system of MRSA, thus achieving inhibition. We found that GA and NGA had anti-MRSA activity in vivo and in vitro and identified saeRS to be the target, indicating that saeRS inhibitors may be used to treat biofilm-related infections.